The Developmental Delay of Seedlings With Cotyledons Only Confers Stress Tolerance to Suaeda aralocaspica (Chenopodiaceae) by Unique Performance on Morphology, Physiology, and Gene Expression - Cao, Jing; Li, Xiaorong; Chen, Ling; He, Meixiang; Lan, Haiyan (Frontiers in Plant Science, 2022)
Cotyledons play an important role in seedling establishment although they may just exist for a short time and become senescent upon the emergence of euphylla. So far, the detailed function of the cotyledon has not been well-understood. Suaeda aralocaspica is an annual halophyte distributed in the cold desert, its cotyledons could exist for a longer time, even last to maturity, they must exert a unique function in seedling development. Therefore, in the present study, we conducted a series of experiments to investigate the morphological and physiological performance of cotyledons under salt stress at different developmental stages. Results showed that the cotyledons kept growing slowly to maintain the normal physiological activities of seedlings by balancing the phytohormone levels, accumulating osmoprotectants and antioxidants, and scavenging reactive oxygen species (ROS) as well; salt stress activated the expression of osmoprotectant-related genes and enhanced the accumulation of related primary metabolites. Furthermore, the differentially expressed transcriptional profiles of cotyledons were also analyzed by cDNA-AFLP to gain an understanding of cotyledons in response to development and salt stress, results revealed a progressive increase in the expression level of the development-related genes, which accounted for the majority of the total tested TDFs; meanwhile, the key photosynthetic and important salt stress-related genes also actively responded. All these performances suggest that the ‘big cotyledons’ are experiencing the delayed but active developmental process, by which S. aralocaspica may survive the harsh condition at the seedling stage.